CORRELATION BETWEEN MENARCHEAL AGE WITH MENSTRUAL HEALTH AWARENESS AMONG COLLEGE STUDENTS IN A PRIVATE UNIVERSITY - Dora Samaria; Theresia Theresia; Doralita Doralita (Universitas Pelita Harapan, 2019)
Adolescent females who had their menarche experience cognitive and psychological development. In that period, it takes adolescents’ awareness of menstrual health in order to behave appropriately and maintains the quality of health. This study aims to identify the correlation between menarcheal age and menstrual health awareness. This research used cross-sectional design done to 117 female students of Economic Education Study Program in Universitas Pelita Harapan from October to November 2017. This research used purposive sampling method. Data were analyzed using Spearman Correlation Test. The results showed that there was a significant correlation between menarcheal age and menstrual health awareness. It can be concluded that adolescents female who had their menarche at normal age (12-14 years) had increased menstrual health awareness. It is recommended for future research to use quasi-experimental or randomized controlled trial study on larger sample size.